Food Riots and the Politics of Provisions in World History. (May 2014) - Bohstedt, John
Summary: The food riots of 2007–8 in dozens of developing countries placed food security on the agendas of the global political economy. Material outcomes remain to be assessed. The problematic of the politics of provisions is: Under what circumstances do the common people's necessities create a political necessity for their rulers to act? What combination of ingredients gives them political leverage (or not)? Food riots (crowd violence: usually seizing food, intercepting carts and barges, or setting prices) set in motion political processes that often led to food relief and/or repression. To riot about food, rioters needed much more than motivations of hunger and outrage, or else world history would consist mostly of food riots. In addition rioters needed both sufficient solidarities to be able to act collectively, and sufficient confidence that the benefits (getting food, both immediately and in more sustained supply) would outweigh the risks and costs of repression and punishment. The latter would be based on reciprocal relationships with the rulers. The outcomes of such 'trials‐by‐ordeal' were then entered into social memory to be consulted in the next crisis. Of course rulers also had their social memories and political calculations. So the 'politics of provisions' – the political economy of food crises and their resolutions – has typically included such components as: political, social, and economic structures; the players' sociopolitical assets, capacities, and relationships; shared ideologies; strategic bargaining in the moment between chief actors; and accidental factors. Those components vary from one time and place to another, so this paper compares the politics of provisions in: pre‐modern England and France; famines in Ireland and India; 'famine‐proofed' Ming and Qing China; Mao's Great Leap Forward Famine; the IMF austerity riots of the 1970s and 80s; and the food riots of 2008, particularly in Egypt, West Africa, and Haiti. The point of such comparisons is not to construct a unified theory of provision politics, but to illuminate significant parameters that shape policies and conflicts over food.